G259(P) A systematic review ofhealth worker-led interventions to reduce mortality in low birth weight neonates in low and middle-income institutional settings. (27th April 2015) - Kesler, E; Costello, A; Heys, M; Azad, K
Abstract : Aim: The majority of the 3.3 million annual neonatal deaths worldwide occur because proven and simple interventions dependent upon skilled human resources are not implemented. 60–80% of these deaths occur in low birth weight (LBW) neonates less than 2.5 kg, with 96.5% of the 20 million LBW neonates being born in the developing world. The aim of this research is to carry out the first systematic literature review on health worker-led interventions to reduce mortality in LBW neonates in institutional settings in low and middle-income (LMIC) countries. Methods: We conducted a systematic review of studies meeting our inclusion and exclusion criteria until October 2014 (Figure 1 ). We searched Pubmed/MEDLINE, Popline, and Cochrane databases utilising a combination of the search terms "low birth weight" or "small for gestational age" and "mortality" and "intervention". We included all studies of health worker led facility-based postnatal interventions in LMIC that assessed the outcome of neonatal mortality in LBW infants. We excluded articles with abstracts not available, articles that were not in English, and research with subjects not human or subjects not infants. Results: We identified six studies reporting LBW neonatal mortality outcomes for health worker led interventions or a package of interventions in institutional settings in LMIC (Table 1 ). We employed the Hierarchy of Evidence framework, which evaluates health care interventions, to rank the strength of research evidence as excellent, good, fair or poor (Table 2 ). Only one study received an excellent ranking, the systematic review on kangaroo mother care (KMC), which included randomised controlled trials that demonstrated a statistically significant decrease in neonatal mortality rates. Conclusion: The literature review demonstrates the limited evidence on health worker-led facility-based postnatal interventions to decrease mortality in LBW infants. Even where adequate evidence exists for impact of interventions on LBW mortality, for example, KMC, there has yet to be consistent scale-up. Further research is necessary utilising more rigorous methodology to ascertain effectiveness of interventions, as well as to identify cost-effective and sustainable strategies to allow for widespread implementation and dissemination of proven interventions.